Cations and hydration in catalytic RNA: molecular dynamics of the hepatitis delta virus ribozyme - Krasovska, Maryna V; Sefcikova, Jana; Réblová, Kamila; Schneider, Bohdan; Walter, Nils G; Sponer, Jirí (Biophysical journal, 2006)
The hepatitis delta virus (HDV) ribozyme is an RNA enzyme from the human pathogenic HDV. Cations play a crucial role in self-cleavage of the HDV ribozyme, by promoting both folding and chemistry. Experimental studies have revealed limited but intriguing details on the location and structural and catalytic functions of metal ions. Here, we analyze a total of approximately 200 ns of explicit-solvent molecular dynamics simulations to provide a complementary atomistic view of the binding of monovalent and divalent cations as well as water molecules to reaction precursor and product forms of the HDV ribozyme. Our simulations find that an Mg2+ cation binds stably, by both inner- and outer-sphere contacts, to the electronegative catalytic pocket of the reaction precursor, in a position to potentially support chemistry. In contrast, protonation of the catalytically involved C75 in the precursor or artificial placement of this Mg2+ into the product structure result in its swift expulsion from the active site. These findings are consistent with a concerted reaction mechanism in which C75 and hydrated Mg2+ act as general base and acid, respectively. Monovalent cations bind to the active site and elsewhere assisted by structurally bridging long-residency water molecules, but are generally delocalized.
Keywords: vodíková vazba; Cations, Monovalent; voda; RNA katalytická; Water; Nucleic Acid Conformation; Molecular Sequence Data; konformace nukleové kyseliny; Base Sequence; Binding Sites; molekulární modely; Magnesium; Hepatitis Delta Virus; virus hepatitidy delta; kationty dvojmocné; sekvence nukleotidů; RNA, Catalytic; hořčík; vazebná místa; Hydrogen Bonding; Sodium; sodík; Cations, Divalent; Models, Molecular; molekulární sekvence - údaje; kationty jednomocné